Eye Movement Features in the Depth and Spatial Perspective Perception of Paintings and Other Static Scenes - Fazlyyyakhmatov, Marsel; Mutagirova, Adelina; Nedopekin, Oleg; Antipov, Vladimir (International Journal of Criminology and Sociology, 2021)
In this paper, using the example of two scenes, they showed that it is possible to perceive the depth and spatial perspective of painting images (and other static scenes) without the condition of binocular disparity (hereinafter referred to as the 3D phenomenon). To study the 3D phenomenon, eye movement is recorded. The students of the Institute of Physics at Kazan Federal University and an experienced researcher of the 3D phenomenon, the author and the developer of the working methodology took part in the surveys on eye movement record. To identify the perception of spatial perspective, 3D raster images are used mounted on the same static stimulus scenes (pictures). The first plot includes obtaining information on eye movement in the conditions of perception of two paintings with the elements of a monocular perspective of images. Histograms show that students perceive the perspective of the pictures displayed on the monitor screen. In two scenes presented, eye focusing occurs outside the plane of stimulus images. When students demonstrate a monitor screen with text and a white sheet of the histogram, they show that the focus planes are located between the screen and the students' eyes.